Effect of subtherapeutic vs. therapeutic administration of macrolides on antimicrobial resistance in Mannheimia haemolytica and enterococci isolated from beef cattle - Zaheer, Rahat; Cook, Shaun; Klima, Cassidy; Stanford, Kim; Alexander, Trevor; Topp, Ed; Read, Ron; Mcallister, Tim (Frontiers in Microbiology, 2013)
Macrolides are the first-line treatment against bovine respiratory disease, and are also used to treat infections in humans. The macrolide, tylosin phosphate, is often included in the diet of cattle as a preventative for liver abscesses in many regions of the world outside of Europe. This study investigated the effects of administering macrolides to beef cattle either systemically through a single subcutaneous injection (therapeutic) or continuously in-feed (subtherapeutic), on the prevalence and antimicrobial resistance of Mannheimia haemolytica and Enterococcus spp. isolated from the nasopharynx and faeces, respectively. Nasopharyngeal and faecal samples were collected weekly over 28 days from untreated beef steers and from steers injected once with tilmicosin or tulathromycin or continuously fed tylosin phosphate at dosages recommended by manufacturers. Tilmicosin and tulathromycin were effective in lowering (P < 0.05) the prevalence of M. haemolytica, whereas subtherpeutic tylosin had no effect. M. haemolytica isolated from control- and macrolide-treated animals were susceptible to macrolides as well as to other antibiotics. Major bacteria co-isolated with M. haemolytica included Pasteurella multocida, Staphylococcus spp., Acinetobacter spp., E. coli and Bacillus spp. With the exception of M. haemolytica and P. multocida, erythromycin resistance was frequently found in other isolated species. Both methods of macrolide administration increased (P < 0.05) the levels erythromycin-resistance enterococci in faeces. Development of resistance to injectable macrolides in bacteria isolated from the nasopharynx was species dependent. Therapeutic administration of tilmicosin and tularthromycin selected for macrolide resistant bacteria within both the respiratory and intestinal tract, whereas suptherapeutic administration of tylosin only selected for macrolide resistance in enteric bacteria.